A Technical Note on Bibliometric Analysis by Biblioshiny and VOSviewer - Himel Mondal (Indian Journal of Radiology and Imaging)
Bibliometric analysis is a powerful tool for mapping and evaluating scientific research publications across various dimensions. Several databases support bibliometric analysis, such as Web of Science and Scopus. However, these are subscription-based resources, which may limit access in resource-constrained settings. In contrast, PubMed is freely accessible and specifically focused on biomedical literature. However, PubMed offers limited analytics, primarily restricted to article types and year-wise publication trends. Despite the limitations, data from PubMed can help in basic bibliometric analysis. This review article provides a basic technical guide to key methods used in bibliometric analysis. The analysis can be conducted for a research topic (e.g., yoga and mental stress), an institution's research output, a journal's publication trends, or an individual author's contributions. For any bibliometric analysis, two components are essential—data and analysis software. For data source, PubMed was used, and two free-to-use tools—Biblioshiny and VOSviewer—were used for analysis. Basic technical procedures are explained with examples. This guide serves as an introductory resource for those seeking to perform bibliometric analysis using freely available tools and data sources.